Inventing Berlin. Architecture, Politics and Cultural Memory in the New/Old German Capital Post-1989. - Dellenbaugh-Losse, Mary (Springer, 2020)
This book comprehensively examines post-1989 changes to the symbolic landscape of Berlin – specifically, street names, architecture, urban planning and monuments – and links these changes to concepts of contested cultural memory and national identity in Berlin and Germany in the post-Wall period. The core of the book is made up of an analysis of built space changes in the eastern half of the city before and after the Berlin Wall, flanked by an introduction to the theoretical underpinnings of the topic and a wider interpretation of the events in Berlin in relation to other geographic and historical contexts. It furthermore offers an explanatory model for the phenomenon of the "symbolic foreigner" whereby former citizens of the GDR feel disenfranchised and excluded from today's German society.
Keywords: Hauptstadtplanung; Stadtentwicklungsplanung; Städtebauentwicklung; Architektur; Städtebau; Identitätsbildung; Nation; Einwohner; Entfremdung; Symbol; Abriss; Denkmal; Platzgestaltung; Postsozialismus; Straßenumbenennung; Sozialistische Stadt